Association of Clinical Symptoms with Biochemical and Hematological Findings in Patients with Tuberculosis. - Ullah Jan, Rahmat; Natarajan, Satheesh Babu; Ali, Nasir (Journal of Neonatal Surgery, 2025)
Objective: Tuberculosis (TB) is a key health issue and is characterized by a wide variety of clinical symptoms which can be affected by the underlying biochemical and hematological status of the patients. Therefore, this study assessed the association of clinical symptoms with biochemical and hematological findings among patients with tuberculosis. Methodology: This cross-sectional experimental study was conducted in institute of Basic Medical Sciences (IBMS), Khyber Medical University. A total of 103 patients aged ≥15 years suspected with pulmonary tuberculosis, were included in the study. A chi-square test and Fisher’s exact test was used to observe the association between clinical symptoms and demographics, hematological, and biochemical findings. Additionally, a Mann Whitney test was employed to analyze the relationship between the means of demographic variables. Results: The study findings showed that all patients reported cough, and 100 (97.1%) had fever, with no significant association between symptoms and demographics, comorbidities, medication use, or hematological markers such as TLC and ESR (p>0.05). Significant associations were found with diabetes, where weight loss 48 (55.2%) (p=0.032) and reduced appetite (p=0.002) were more common among diabetics. Reduced appetite was also significantly linked to fasting blood sugar levels (p=0.017) and chronic illness (p=0.020), while all other variables showed no significant associations. Conclusion: This study concluded that comorbid diabetes and chronic illnesses were significantly associated with main clinical symptoms, such as weight loss and reduced appetite. A significant association was identified between fasting blood sugar levels and reduced appetite. In contrast, hematological parameters including Total Leukocyte Count (TLC) and Erythrocyte Sedimentation Rate (ESR), showed no significant association with clinical symptoms